Antibacterial and Antiadhesion Effects of Psidium guajava Fractions on a Multispecies Biofilm Associated with Periodontitis - Pablo Alejandro Millones Gómez; Margarita Fe Requena Mendizábal; Roger Damaso Calla Poma; Tania Valentina Rosales Cifuentes; Federico Martin Malpartida Quispe; Dora Jesús Maurtua Torres; Reyma Evelyn Bacilio Amaranto; Carlos Alberto Minchón Medina; Lusin Antonio Ponce Contreras (Association of Support to Oral Health Research (APESB), 2022)
Objective: To assess the antibacterial activity of Psidium guajava fractions and their effects on adhesion of a multispecies biofilm consisting of Streptococcus gordonii, Fusobacterium nucleatum, and Porphyromonas gingivalis in vitro. Material and Methods: Guava leaves were obtained from the mountains of northern Peru, where they grow wild and free of pesticides. The antimicrobial activity of 25 mg/mL petroleum ether, 25 mg/mL dichloromethane and 25 mg/mL methanol fractions of P. guajava was evaluated by measuring inhibition halos, as well as the effect on the adhesion of multispecies biofilms at 4, 7 and 10 days of growth by measuring the optical density. In addition, antimicrobial susceptibility was compared using the Kruskal-Wallis test and its multiple comparison tests, and differences in mean biofilm adhesion between each fraction were assessed by repeated measures analysis and the Tukey multiple comparison test. Results: The rank-based Kruskal-Wallis test highlighted differences in the effects of the fractions on the zone of inhibition for each oral bacterium, including S. gordonii(p=0.000), F. nucleatum (p=0.000), and P. gingivalis (p=0.000), the Tukey test showed that the group treated with 0.12% chlorhexidine exhibited the least amount of adhesion, followed by the group treated with the 1.56 mg/mL methanol fraction. Conclusion: The methanol fraction of P. guajava had an antibacterial effect on S. gordonii and P. gingivalis, and the 1.56 mg/mL methanol fraction decreased biofilm adhesion.